Incidence Of Kras Mutations In Colon Adenocarcinomas And Its Association With Lymph Node Metastases - Varlı, Gökhan; Özercan, İbrahim Hanifi; Önalan, Ebru (Hitit Üniversitesi, 2020)
Objective: Colon adenocarcinoma, one of the most frequent malignant tumors of the gastrointestinal system, is a major cause of morbidity and mortality. As KRAS mutations are encountered in 30-40% of colorectal carcinomas, a mutation screening is required before therapy commences. In this study, we aim to determine KRAS codon 12, 13 and 61 mutations in moderately differentiated colon adenocarcinomas and assess whether these mutations are associated with lymph node metastases. Materials and methods: A total of 120 moderately differentiated colorectal carcinomas, 60 with lymph node metastases and 60 without, were included. Samples underwent PCR with appropriate primers and Sanger sequencing was carried out to determine their KRAS mutation status. Results: Out of the 120 cases included in our study, 40 carried codon 12, 5 carried codon 13 mutations. In total, 37.5% of cases had a KRAS mutation (45/120). No mutation was detected in codon 61. Conclusion: Our study has not shown a significant association between the presence of KRAS mutations and lymph node metastasis. This study was conducted in a limited number of patients and in a pre-defined, small area; but can be used as a preliminary step for multicenter and larger studies.

Amaç: Gastrointestinal sistemin en yaygın malignitesi olan kolon kanserleri mortalite ve morbiditenin ana nedenlerinden biridir. Kolorektal kanserlerin %30-40’ında KRAS gen mutasyonu izlendiğinden tedaviye başlamadan önce mutasyon taraması önemlidir. Bu çalışmadaki amacımız orta derece diferansiye kolon adenokarsinomlarında KRAS kodon 12, 13, 61 mutasyon durumunu belirlemek ve bu mutasyonların lenf nodu metastazı ile ilişkisini araştırmaktır. Gereç ve yöntem: Fırat Üniversitesi Tıp Fakültesi Tıbbi Patoloji Anabilim Dalı arşivinden seçilen 60 adet lenf nodu metastazlı ve 60 adet lenf nodu metastazı olmayan toplam 120 adet orta derecede diferansiye kolon adenokarsinomu örneğinden uygun primer çiftleri PZR ile çoğaltılıp sekans analizi ile KRAS mutasyon durumu belirlenmiştir. Bulgular: Çalışmamıza alınan 120 olguda 40 tanesi kodon 12 de ve 5 tanesi kodon 13 de olmak üzere %37.5 (45/120) oranında KRAS mutasyonu izlendi. KRAS kodon 61 de mutasyona rastlanmadı. Sonuç: Çalışmamızda KRAS mutasyon durumu ile lenf nodu metastazı arasında anlamlı bir ilişki bulunmadı. Bu çalışma küçük bir alanda öncesinde tanı almış sınırlı sayıda olguda yapıldı; ancak çok merkezli ve daha geniş çalışmalar için bir ön izlenim taşıma özelliğindedir.
Kolon Adenokarsinomlarinda Kras Mutasyonlarinin Sikliği Ve Lenf Nodu Metastazi İle İlişkisi
Keywords: Clinical Sciences; Klinik Tıp Bilimleri